2013
DOI: 10.1128/jvi.01834-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Bridging-Sheet Recruitment Explains HIV-1 R5 Envelope Glycoprotein Sensitivity to Soluble CD4 and Macrophage Tropism

Abstract: h HIV-1 R5 viruses vary extensively in their capacity to infect macrophages. R5 viruses that confer efficient infection of macrophages are able to exploit low levels of CD4 for infection and predominate in brain tissue, where macrophages are a major target for infection. HIV-1 R5 founder viruses that are transmitted were reported to be non-macrophage-tropic. Here, we investigated the sensitivities of macrophage-tropic and non-macrophage-tropic R5 envelopes to neutralizing antibodies. We observed striking diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 61 publications
4
36
0
Order By: Relevance
“…1a). Previous studies have reported that M-tropic variants are also more sensitive to sCD4 than T-tropic variants (27)(28)(29). We confirmed this observation by showing that M-tropic variants were on average 27-fold more sensitive to sCD4 than their T-tropic counterparts (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…1a). Previous studies have reported that M-tropic variants are also more sensitive to sCD4 than T-tropic variants (27)(28)(29). We confirmed this observation by showing that M-tropic variants were on average 27-fold more sensitive to sCD4 than their T-tropic counterparts (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…4c), suggesting that M-tropic viruses may differ in the Env protein conformation of the V1/V2 region, which is now understood to be highly ordered (52,98) and is thought to contribute to the structure and function of the Env trimer (99)(100)(101)(102)(103). Although our ability to assign significance to V1/V2 antibody resistance as a feature of macrophage tropism is limited by sample size (n ϭ 7) and the inherent variability to the neutralization of primary isolates, this observation is consistent with another obtained using a larger panel of unpaired T-tropic and M-tropic viruses (29). Overall, the neutralizing antibody sensitivity properties of M-tropic Env proteins reveals them to be more like R5 T-tropic Env proteins than tissue culture-adapted variants, but with intriguing differences in the CD4bs and perhaps the V1/V2 loop region.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Of note, the mutations that lead to adaptation to mCD4 also confer the ability to use smaller amounts of the human CD4 receptor for entry (18). Interestingly, previously described variants capable of infecting cells expressing small amounts of CD4 exhibit antigenic properties similar to those identified for A204E and G312V mutant proteins, including resistance to PG9/PG16 and sensitivity to 447-52D (56). Taken together, the results suggest that HIV-1 Env variants may experience similar selective pressures and resulting conformational changes as they adapt to cells expressing either mCD4 or small amounts of human CD4.…”
Section: Figmentioning
confidence: 98%
“…Consequently, CD4 independence may be a previously unappreciated property of some SIVsm Env variants, such as E660.11, that could influence neutralization sensitivity, transmission, and pathogenesis and should therefore be evaluated when selecting a neutralization panel or a challenge virus. We also evaluated susceptibility to inhibition by human sCD4, which can be an indicator of such properties as CD4 contact residue exposure, affinity for the CD4 receptor, CD4-induced formation of the bridging sheet, and Env stability (74,75). Most of the SIVsm Envs had intermediate sensitivity to sCD4 inhibition (Fig.…”
Section: Characteristics Of Sivsm Env Panel Siv-based Vaccine Effortsmentioning
confidence: 99%